Racial Hatery Portrayed in the Movie “Till” (2022): A Sociological Approach - Dimas Yogi Thoriqul Maulana; Nugroho, Abdillah (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
The purpose of this research is to explain how racism against black people is portrayed in the movie Till (2022), analyze the impacts of racism, and the resolution of that racism. This research is a literary study research with a sociological approach. The results of this research show that the level of racism that occurs is very high. Racism is seen when the prejudice and hatred of white people is shown towards black people. The great hatred of black people led white people to go so far that it led to murder. Even after the murder, there was no justice for black people, it was shown that justice was more on the side of white people. Suffering and injustice encourage black people to fight for their rights as humans in order to live better. Racism as a whole has a very bad impact on the people affected, especially minorities, they will be looked down upon and treated arbitrarily. It is hoped that this research can increase understanding of the acts of racism depicted in the movie Till and aims to increase people awareness by examining the depiction of racism in the movie.